REALITY OF HUBRIS SYNDROME THROUGH HERMAN MELVILLE’S NOVEL MOBY DICK - Hidayati Hidayati; Arifuddin Arifuddin; Aflina Aflina; Ratna Sari Dewi (Universitas Islam Sumatera Utara, 2021)
Exposing hubris syndrome, a behavior pattern that is not in accordance with the norms of standard behavior and becomes part of a mental disorder is the objective of the study. This syndrome usually occurs in someone with power in hand, tending to be tyrannical and feeling to be always right. In the study of literature Hubris syndrome refers to the tragic flaw that brings a person, usually an important figure, to a self-destruction. Hubris syndrome can occur to anyone. The method used is descriptive qualitative tied to things experienced by the community termed a social phenomenon. The results show that the central figure in this novel, a captain of a whale hunting vessel, experiences hubris syndrome with three prominent patterns of behavior: narcissistic propensity, excessive confidence and loneliness. In the first pattern, the person concerned feels like a superhuman deserving to be admired and attended to. The second, excessive self-confidence cannot be accepted by rational thinking. The third is the consequence of the first two patterns of living a life of solitude because of losing contact with the surroundings. The storyline ends tragically; the entire crew is killed by the whale and only one left and becomes a narrator. Hubris syndrome in the novel is a reality meaning that anyone who has a certain position tends to have Hubris syndrome and this is in line with the findings in the field with a percentage reaching 92.